Analysis Of Public Satisfaction With Public Services Based On The Public Satisfaction Index (Ikm) At Pgar Jati Treatment Puskesmas, Pagar Jatika District, Central Bengkulu Regency - Desmanto Desmanto; Karona Cahya Susena; Nurzam Nurzam (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
The research objective was to determine community satisfaction with public services based on the community satisfaction index (IKM) at the Pagar Jati Care Health Center, Pagar Jati District, Central Bengkulu Regency. The data analysis technique used was to measure the value of the Community Satisfaction Index (IKM) based on the Regulation of the Minister of Administrative Reform and Bureaucratic Reform Number 14 of 2017. The sample in this study was 191 patients who received services from the Pagar Jati Treatment Health Center, Pagar Jati District, Regency Central Bangalore.The Community Satisfaction Index (IKM) for the quality of service at the Pagar Jati Health Center, Pagar Jati District, Central Bengkulu Regency obtained an average value of 3.18 which is in a good assessment. Furthermore, the IKM for service units is multiplied by 25 so that the IKM at the Pagar Jati Care Health Center, Pagar Jati District, Central Bengkulu Regency is 79.38 with service quality B with good criteria because it is in the value interval of 76.61 – 88.3. The element of cost/tariff gets the highest rating with an average score of 3.53 with very good assessment criteria. This illustrates that patients assess the Pagar Jati Care Health Center, Pagar Jati District, Central Bengkulu Regency to provide services free of charge. The lowest satisfaction score is 2.64, namely the completion time with poor assessment criteria. This illustrates that the lack of speed in service is caused by a lack of medical personnel or existing health workers, while there are quite a lot of people asking for health services, causing delays in providing health services to the community.